If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5X + -7X = 7X + 23 Combine like terms: -5X + -7X = -12X -12X = 7X + 23 Reorder the terms: -12X = 23 + 7X Solving -12X = 23 + 7X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7X' to each side of the equation. -12X + -7X = 23 + 7X + -7X Combine like terms: -12X + -7X = -19X -19X = 23 + 7X + -7X Combine like terms: 7X + -7X = 0 -19X = 23 + 0 -19X = 23 Divide each side by '-19'. X = -1.210526316 Simplifying X = -1.210526316
| 2x^3-x^2-6x+3=0 | | 5x+9=6-2x | | (-5xy)+(-2x)= | | 0.3(x+9)=15 | | x^3+3x^2-10x-24=0 | | y^3-14y^2=y-14 | | 12x*5-7/2=18x+5 | | 4x^2+1=2 | | 4p+6=-30 | | 83-2x=8+23 | | 7x-1=6x-4 | | 2-5x=7x+110 | | P-13=13 | | 4x+14=9-5x | | 2.2a=55 | | 82-4x=32x+18 | | 168=6y | | 7x+5-4=9+6x | | 9-7x=164-42x | | 7z-13=15 | | -123-8x=10x+21 | | 3s+2=14(s-1) | | 10p+q-11-p=-2(2p+4)-3(2p-2) | | -6-5=6-8x | | -2x+3=25 | | 3x+18+c=-12-3x+2 | | I(f)=12f | | 4b^2-3b-8=0 | | c=55.55(59-32) | | 0=x^3-3x^2-x+3 | | 2r^2-8=0 | | x+x+12=5x |